Digital World Bug: Y2k38 an Integer Overflow Threat-Epoch - Harshini, S; Kavyasri, KR; Bhavishya, P; Sethukkarasi, T (International Journal of Computer Sciences and Engineering, 2025)
Digital universe has been menaced by plenty of bugs but only a few seemed to pose a great hazard. Y2K,Y2K10 were the most prominent bugs which were blown away. And now we have Y2K38. The Y2K38 bug, if not resolved, it will get hold off the predictions that were made for the Y2K bug would come face reality this time. Y2K38 bug will affect all the system applications and most of the embedded systems which use signed 32 bit format for representing the internal time. The number of seconds which can be represented using this signed 32 bit format is 2,147,483,647 which will be equal to the time 19, January, 2038 at 03:14:07 UTC(Coordinated Universal Time),where the bug is expected to hit the web. After this moment the systems will stop working correctly. This could wipe out programs that rely on the internal clock to make measurements. There have been some solutions which delayed this problem, that we can have some more time to find a universal solution and so does our proposed solution.